2018
DOI: 10.1111/bju.14530
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐operative and local control outcomes of robot‐assisted partial nephrectomy vs percutaneous cryoablation for renal masses: comparison after matching on radiological stage and renal score

Abstract: The local recurrence rate after PCA was significantly higher than after RAPN for T1 renal tumours. Incomplete treatment was the main criterion associated with recurrence. The recurrence rate may have been overestimated in the PCA group because of closer radiological follow-up in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…The mean follow-up period of every group in all studies was up to 6 months. 8 eligible studies got a score ≥ 7 according to Newcastle-Ottawa Scale (Table S1) 8, 14, 16-18, 20, 24, 25, while the remaining ones were marked as moderate quality studies 2, 3, 10, 13, 19, 21-23, 26. Most studies did not describe clearly about how to deal with missing data or intention-to-treat analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The mean follow-up period of every group in all studies was up to 6 months. 8 eligible studies got a score ≥ 7 according to Newcastle-Ottawa Scale (Table S1) 8, 14, 16-18, 20, 24, 25, while the remaining ones were marked as moderate quality studies 2, 3, 10, 13, 19, 21-23, 26. Most studies did not describe clearly about how to deal with missing data or intention-to-treat analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the oncological outcomes, our series showed 0.8% of recurrences and 0.7% of metastases within a median follow-up of 37 mo, which is limited. Fraisse et al [31] reported an absolute recurrence rate of 8.4% in patients, who underwent percutaneous cryoablation, with a mean clinical tumor size of 25.9 cm and a mean follow of 5 yr.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, RAPN is more useful than open partial nephrectomy and laparoscopic partial nephrectomy 3 . And the local recurrence rate of T1 renal tumors after renal cryoablation was significantly higher than that after RAPN 4 . Although there have been reports of RAPN in horseshoe kidney for benign tumor and heminephrectomy using a robotic device, 2 there have been no reports of RAPN for renal cell carcinoma in a horseshoe kidney, in particular, that treated via a retroperitoneal approach (Table 1).…”
Section: Discussionmentioning
confidence: 99%